Assessment of the Health Status of Oak Trees in the Zouagha Forest (North-East of Algeria) - Chouiter Norhane; Rached-Kanouni Malika; Boucif Ouarda El Wahida (Ekológia (Bratislava))
The objective of this study is to assess the health status of the Zouagha forest in Algeria, which is composed of oak trees (Quercus suber, Q. canariensis, and Q. afares), and to estimate its biodiversity potential through field observations using the ARCHI, DEPEFEU, and IBP methods on individuals of each species. The adopted methodology relies on a visual evaluation of the tree crowns of the main species in this forest. The results indicate that the health of tree crowns is moderate, as is the biodiversity carrying capacity according to the IBP rating scale. Within the ARCHI protocol, two distinct types can be observed: ARCHI type R (Resilient), characterized by proportions of 42.72% for Q. suber, 40.7% for Q. canariensis, and 45% for Q. afares, and the ARCHI type S (Healthy), with slightly different proportions, namely 38.18% for Q. suber, 38.05% for Q. canariensis,and36%forQ. afares. Regarding the DEPEFEU protocol, it is important to note that the average health condition class has percentages of 37.27% for Q. suber, 32.74% for Q. canariensis, and 39% for Q. afares. Therefore, it is imperative to implement appropriate forest management strategies to ensure the sustainability of forest ecosystems. These strategies should aim to preserve the ecological integrity of the Zouagha forest in Algeria, with a focus on the regeneration of oak species (Q. suber, Q. canariensis, and Q. afares) and the restoration of their health.